Increased Cardiovascular Risk in Patients with Adrenal Insufficiency: A Short Review. (10th December 2017) - Rahvar, Amir-Hossein; Haas, Christian S.; Danneberg, Sven; Harbeck, Birgit
Abstract : Cardiovascular disease (CVD) is the most common cause of death in the world. Recent studies have shown an association between adrenal insufficiency (AI) and increased cardiovascular risk (CVR). Patients with AI receive glucocorticoid (GC) replacement therapy which can lead to varying levels of blood cortisol. It was shown that these imbalances in blood cortisol may lead to a higher prevalence of coronary heart disease, major adverse coronary events, and increased mortality. GC substitution is essential in the treatment of AI without which the disease has been shown to be fatal. The most frequently used GC formula for replacement therapy is hydrocortisone (HC). There is no uniform opinion on hydrocortisone replacement therapy. Alternative GC such as prednisolone is also in use. Overreplacement of GC may lead to adverse effects including obesity, high blood pressure, and hyperglycaemia. Outcome may vary between primary and secondary AI mainly due to differences in the renin-angiotensin-aldosterone system (RAAS). Furthermore, decreased blood levels of cortisol may lead to a compensatory secretion of inflammatory mediators such as Interleukin-1 (IL-1), Interleukin-6 (IL-6), and/or tumor-necrosis factor (TNF). Physicians and patients should be properly educated about the increased risk of CVD in patients with AI.